Firm migration in the Netherlands - Pieter Hendrik Pellenbarg (European Regional Science Association (ERSA), 2005)
The paper surveys what is known from various data sources about the process of firm migration in the Netherlands. The availability and quality of data sources concerning firm migration are discussed, just as the development of firm migration processes in the past decades, and the impact of firm migrations on regional economic structures and regional employment. This impact is then compared with the impact of other firm demographic components, i.e. new firm establishments, and firm closures. Then the regional patterns of firm migration are shown – to the extent that the data sources allow - with a focus on the movements in and out of the national economic core region (the Randstad). Especially for the sector of manufacturing industry we witness a gradual change, from a clear-cut core-periphery deconcentration pattern in the past to a more erratic pattern at present. This is related to a gradual change in the main migration motives, from labour market shortages to lack of space and accessibility, and from hard to soft location factors. Finally the paper addresses the role of government policies in guiding firm migrations to policy assisted regions and locations.
Keywords: 330